Modelamento do fluxo de água subterrânea na área da unidade de concentração de urânio, município de Caetité - Bahia - Azevedo, Lucia Ferreira de (2006)
Waste generated from mining and milling of uranium ores contains low concentrations of radioactive material, but is generated in large quantities. Due to presence of long-lived radionuclides associated with the waste, the final disposal facilities have to be effective for long periods of time. It is important the groundwater flow characterization in the sense that groundwater is the main medium which can transport radionuclides by natural processes from disposed waste to the environment. The objective of this work was to characterize the groudwater flow on the Uranium Concentration Facilities (URA) site operated by the Indústrias Nucleares do Brasil (IN B) located at the municipality of Caetité, Brazil. This research presents a groudwater flow modelling at URA site, using the MODFLOW code. This code simulates three-dimensional, stead-state or transient groudwater flow in confined or unconfined, heterogeneous and anisotropic porous media with variable layer thicknesses. The necessary parameters to simulate the flow were estimated using specific studies about the site. The geological and hydrogeological studies show that in this area the groundwater is stored in fractured crystalline rocks with a fine mantle of weathering. The area topography is accentuated, with altitudes varying from 765 to 980 meters, with typical vegetable covering of the savanna of the semi-arid and an annual average precipitation of 732 mm, with high evapotranspiration and water deficit. The boundary condition of constant head was used in the west and midleeast limits of the model and of no flow, in northeast and southeast borders. To represent the lateral flow in the limits south and north of the model was established the boundary type GHB. In addition to those conditions, the boundary of the type drain was established for the sreams and the type river to the dam. The hydraulic conductivity evaluated for aquifer formation was 4.91 x 10-5 cm/s and in the more fractured zone was 1,51 x 10-4cm/s. The average annual rate of recharge was estimated from hydrologic balance in 40mm. The potentiometric map generated using the MODFLOW code showed a good agreement between the hydraulic head simulated and that measured in the field. As a final product it was presented the capture zone of the wells and the tracking of particles simulating the release of radioactive pollutants in the groundwater.